Formulation and Shelf-Life Estimation of Ready-to-Drink Avocado Coffee Milk and Durian Coffee Milk Products - Muhandri, Tjahja; Yufriyana, Nur; Suyatma, Nugraha Edhi; Sugihartini, Rahayu Lestari (Universitas Djuanda, 2025)
Coffee is widely and regularly consumed in Indonesia. The trend towards practical lifestyle has driven the development of ready-to-drink (RTD) coffee products. Avocado and durian are commonly incorporated as additives due to their unique flavor profiles, creamy textures, and potential to enhance the functional properties of coffee-based drinks. This study aimed to identify the optimal formulation of RTD avocado coffee milk and durian coffee milk products based on sensory characteristics and to estimate their shelf life using the direct method. The formulations were developed by varying the fruit purée concentration: 5%, 7.5%, and 10% for avocado coffee milk, and 5%, 10%, and 15% for durian coffee milk. The hedonic rating test revealed that formulations containing 5% avocado purée and 15% durian purée were the most preferred by 50 panelists. These selected formulations were further analyzed to estimate product shelf life at 4°C and 18°C. Quality changes were evaluated through objective parameters (color change [∆E], pH, viscosity, and physical stability) and subjective parameters (color, aroma, and flavor intensities). Products stored at 18°C deteriorated more rapidly and were excluded from further shelf life prediction. The estimated shelf life of avocado coffee milk stored at 4°C was 59 days based on flavor parameter (R² = 0.9338), while durian coffee milk had an estimated shelf life of 61 days based on pH (R² = 0.9305).